A Semantic Analysis of Sentence, Utterance, and Presupposition in The Short Story “The Necklace” By Guy De Maupassant - Anggita Tiara Apriliani; Naila Rahmawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study explored the semantic components of presupposition, speech, and phrase in Guy de Maupassant's short story "The Necklace. " The researcher uses a descriptive qualitative method to identify instances of sentences that highlight the distinction between structure (sentences) and actual speech acts (utterances), and to examine the kinds of presuppositions that may be drawn from pragmatic theory. The findings show that various sentences in storytelling and dialogue express different concepts depending on the circumstances and setting. In addition, a wide range of assumptions were found, including lexical, empirical, and existential. The relationship between the language structure of narrative works and their meaning is further understood via this study.